Enemies at the Gateway: Regional Populist Discourse and the Fight Against Oil Pipelines on Canada's West Coast - Neubauer, Robert; Gunster, Shane (Frontiers in Communication, 2019)
This paper explores discursive strategies of opponents of the Northern Gateway pipeline and tanker project – a proposal to link Alberta oil sands producers to international markets via Canada’s West Coast. It explores how regional concerns about Northern Gateway helped galvanize a movement led by regional First Nations, environmentalists, and settler communities, all of whom opposed Gateway as a means to protect regional ecosystems – and the local communities dependent on them – from “extra-regional” Gateway-backing elites. By articulating arguments against Northern Gateway with salient collective action frames concerning ecological sustainability, regional identity, Indigenous sovereignty, social justice, and democratic agency, this anti-Gateway ‘discourse coalition’ helped contribute to the project’s ultimate collapse in 2016. In this paper, we critically engage with Ernesto Laclau’s theorization of populism to analyse this movement as a form of “regional ecological populism”, explaining how a shift in spatial framing from the national to the regional enabled a particular variant of populist discourse to emerge. Furthermore, we relate Laclau’s framework to Hajer’s concept of discursive “storylines” and Gamson’s analysis of “collective action frames” to pivot away from Laclau’s focus on the ontological construction of unified popular subjects to a more grounded analysis of how coalitions articulate populist storylines designed to mobilize diverse movement constituents. In doing so, we draw on a frame analysis of communications materials produced by several prominent First Nations and environmental organizations publicly mobilizing against Northern Gateway between 2010 and 2015, tracing how these groups came to articulate a common regional ecological populist storyline. Finally, we end with some thoughts about the possibilities and challenges for scaling up regional ecological populism in Canada.